Bahasa Cinta: Tinjauan Dari Perspektif Filsafat Hans-Georg Gadamer - Pristica, Bela; Virgin, Diah; Sitorus, Fitzerald Kennedy (CV. ITTC INDONESIA, 2023)
One sees language as an arbitrary system of symbolic sounds in the language of Love. Learning a language does not only mean learning to use existing tools to refer to a familiar world; it also means becoming familiar and intimate with the world itself and how it confronts us. The methods used are based on literature analysis, text analysis, and perspective analysis approaches. The results of this study show that Hans-Georg Gadamer has improved our understanding of the language of love. Love languages include Physical Touch, Words of Affirmation, Quality Time, Gifts, and Acts of Service..